"Vertical structure of the Arctic spring transition in the middle atmosphere" - Matthias, Vivien; Stober, Gunter; Kozlovsky, Alexander; Lester, Mark; Belova, Evgenia; Kero, Johan (Journal of Geophysical Research: Atmospheres, 2021)
In the middle atmosphere, spring transition is the time period where the zonal circulation reverses from winter westerly to summer easterly which has a strong impact on the vertical wave propagation influencing the ionospheric variability. The spring transition can be rapid in form of a final sudden stratospheric warming (SSW, mainly dynamically driven) or slow (mainly radiatively driven) but also intermediate stages can occur. In most studies spring transitions are classified either by their timing of occurrence or by their vertical structure. However, all these studies focus exclusively on the stratosphere and it is not clear if and how pre-winter conditions have an impact on when and how spring transitions take place. Here we classify the spring transitions regarding their vertical-temporal development beginning in January and spanning the whole middle atmosphere in the core region of the polar vortex. This leads to five classes where the timing of the SSW in the preceding winter and a downward propagating Northern Annular Mode (NAM) plays a crucial role. First, we use MLS satellite data to describe the five classes for recent single years, and then we use MERRA-2 reanalysis data for a composite analysis. The results show distinctive differences between the five classes in the months before the spring transition especially in the mesosphere. We hypothesize that this will help to improve the prediction of the spring transition. Additionally, meteor radar winds are used to link spring transition effects in the upper mesosphere and lower thermosphere with the stratospheric final warming.